La prévention active des sinistres : un point de vue industriel - Havers, J.N. (Assurances, 1985)
Some insureds do not seem to realize that they can indeed prevent, in their homes or businesses, losses which could prove costly in terms of delays and indemnities. At the annual Rendez-Vous de Septembre which is attended in Monaco by some 2,000 insurers, reinsurers and brokers from around the world, the theme this year was Loss Prevention. The organizers of the Rendez-Vous called upon three speakers to stress the importance of active prevention, as it is called. Following is the text of the speech given by Mr. J.N. Havers, Risk Manager for Dunlop of England. Though Mr. Havers only outlined the problem, he nevertheless brought out certain aspects which may be useful to the reader. In particular, he deals with the central issue of this recurring concern which insurers and, fortunately, insureds share, at least in the case of large buildings where sizeable amounts of capital are at stake. As pointed out by Mr. Havers, to obtain fruitful results, the collaboration of both parties, the insurer and the insured, is indispensable, be it with respect to fire, theft, automobile and public liability insurance. As we are well aware, public liability claims involve increasingly large amounts each year. Mr. Havers pointed out certain measures an insured might take to avoid bodily injury or property damage which could exceed acceptable limits for insurers. We will never forget the terrible consequences of thalidomid-causing drugs and the countless claims due to asbestosis. Though Mr. Havers does not offer a panacea of specific guidelines, he does remind us of the seriousness of the risks involved and the importance of active collaboration between insurer and insured.